KONSEP PENDIDIKAN AKHLAK PERSPEKTIF AL-QUR’AN SURAH LUQMAN AYAT 13-19 (STUDI AL-QUR’AN SURAH LUQMAN AYAT 13-19 DI DALAM TAFSIR AL-QURTHUBI) - Maula, Fatchiyanni Ashviyaul; Ridlwan, Burhanuddin; Salim, M Nur (EL-Islam, 2025)
Abstract: The moral crisis that has begun to occur in the modern and sophisticated era like today shows that moral education needs to be improved. The moral education applied by Luqman to the Qur'an needs to be revisited. This research aims to recognize the concept of moral education listed in surah Luqman verses 13-19 with the view of the interpretation of Al-Qurthubi. The type of research is a literature study. Literature study is a series of activities that involve recording data from literature sources, reading, recording, and processing material for research purposes. The results of the study stated that the moral education that is emphasized contains morals towards Allah, morals towards oneself, and morals towards fellow humans. The values of manners contained include believing in Allah, respecting parents, doing prayers, spreading goodness and removing evil, being careful in doing deeds, not being arrogant and humble towards fellow humans.